2001
DOI: 10.1046/j.1365-4362.2001.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary henna tattoo reactions in children

Abstract: Case 1 A 9‐year‐old girl applied a temporary henna tattoo to her right arm and 1 week later repeated the same process. In the following 2 days, erythema and papulovesicular eruptions developed at the application site (Fig. 1). Patch tests were performed with the European Standard Series, specific hairdressing agents, and commercial and natural henna. The patient showed a 3+ reaction to both natural henna and ‘‘para‐phenylenediamine (PPD)’' 1% and a 3+ reaction to nickel sulfate 5% at 48, 72, and 96 h (Fig. 2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
0
35
0
4
Order By: Relevance
“…It is added to henna to speed up dyeing and to improve pattern definition. It has been known as a strong, delayed type skin sensitiser 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…It is added to henna to speed up dyeing and to improve pattern definition. It has been known as a strong, delayed type skin sensitiser 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…Compared to a permanent tattoo, TBHT is commonly considered to be more advantageous because there is no associated pain or risk of infection, and although it leaves a mark, it disappears after a few weeks and can be reapplied if desired [13,14,15]. For all these reasons, parents who authorize their children to receive the tattoos consider it a natural practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the Food and Drug Administration has found PPD concentrations in henna ranging from 4.9% to 27.2% [19]. In addition to the high and, in some cases, unknown concentrations of PPD in henna tattoos, there are other elements that can promote sensitization: prolonged contact with the skin and the lack of an oxidizing substance that neutralizes the effect; the use of oils or solvents; a hot environment that increases the local temperature of the skin facilitating the percutaneous penetration; the use of syringes to apply the dye; the use of occlusive dressings to keep the henna attached to the skin; and the retouching of tattoos [15,20]. Some of these factors could have played a role in both of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature on these reactions revealed a few reported cases in dermatology, allergy, and pediatrics' journals [1][2][3][4][5][6][7][8][9] and none in the hand or plastic surgery literature. The aim of this communication is to increase the awareness of plastic surgeons to these skin reactions and their management.…”
Section: To the Editormentioning
confidence: 99%